Hardiness pada Penderita Kusta - Denny Elvan Ardhi (Universitas Trunojoyo Madura, 2017)
This study aims to reveal the hardiness of leprosy patients in the village of Tanjung Kenongo, Sumber Glagah sub village, Mojokerto. This study uses qualitative research with case study approach. Subjects in this study are two with purposive sampling techniques and methods of collecting data using semi-structured interview technique. Analysis technique used in this study is a model of Miles and Huberman include data collection, data reduction, data presentation, and conclusion. The result of the research show that the leprosy patients filled showed by 3 aspect of hardiness. The first that control aspect, leprosy patients can control them self and influence all events that happened in their life with accept the reality and be patient of their hardships of life. Second that commitment aspect, the leprosy patients can involve them self to the society with following the social activity and found the meaning of their event in their life. Last that challenge aspect, the leprosy patients with the physical limitations can help the family economic and showed the attitude if they want have better relationship with their family that refuse them.Keywords: Hardiness, the leprosy patient, Sumber Glagah sub village